2017
DOI: 10.1071/fp16370
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of soil salinity and high temperature on photosynthesis and growth of quinoa plants (Chenopodium quinoa)

Abstract: The halophytic crop quinoa (Chenopodium quinoa Willd.) is adapted to soil salinity and cold climate, but recent investigations have shown that quinoa can be grown in significantly warmer latitudes, i.e. the Mediterranean region, where high temperature and soil salinity can occur in combination. In this greenhouse study, effects of saltwater irrigation and high temperature on growth and development of the Bolivian cultivar ‘Achachino’ were determined. Development was slightly delayed in response to saltwater tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 74 publications
8
55
1
Order By: Relevance
“…The same results were reported in the quinoa cv. “Achachino” at day/night temperatures of 28/20°C (Becker et al., ). The number of branches in sorghum increased under a temperature of 36/26°C; however, when the temperature was increased to 40/30°C, the number of branches was reduced (Prasad, Boote, & Allen, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same results were reported in the quinoa cv. “Achachino” at day/night temperatures of 28/20°C (Becker et al., ). The number of branches in sorghum increased under a temperature of 36/26°C; however, when the temperature was increased to 40/30°C, the number of branches was reduced (Prasad, Boote, & Allen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the seed yield of the quinoa cv. “Achachino” increased at high temperature (28/20°C) when the plants were watered with freshwater, but there were no differences observed when the plants were watered with saltwater (Becker et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 °S), and further improved in European material leading to European cultivars from the Netherlands and Denmark (Galwey, ; Jacobsen, , ; Jacobsen & Stølen, ). It is concluded that a strong, daylength sensitive, stay green reaction is the main cause of the late maturity of South American quinoa accessions in North Europe (Adolf, Shabala, Andersen, Razzaghi, & Jacobsen, ; Becker et al., ; Christiansen et al., ).…”
Section: Crop Adaptationmentioning
confidence: 99%
“…Among genotypes the reduction in SPAD Value due to the given combined stress was highest in genotypes HD-2985, HT-8 and HI-1563 (41.8, 29.0 and 41.6 respectively) and least reduction in genotypes KRL-19, HD-2733 and KRL-1-4 (13, 12.6 and 14.5% respectively). Becker et al, 2017 also studied the effects of combined soil salinity and high temperature on photosynthesis and growth of quinoa plants (Chenopodium quinoa). Thus wheat genotypes KRL-19, HD-2733 and KRL-1-4 were considered as tolerant as they were able to tolerate the different stress interactions and genotypes HD-2985, HT-8 and HI-1563 were considered as susceptible.…”
Section: Spad Valuementioning
confidence: 99%